Automated synthesis of 1-[11C]acetoacetate on a TRASIS AIO module. (November 2017) - Solingapuram Sai, Kiran Kumar; Donald Gage, H.; Almaguel, Frankis; Neth, Bryan; Hughes, Timothy M.; Tremblay, Sebastien; Castellano, Christian-Alexandre; Cunnane, Stephen C.; Jorgensen, Matthew J.; Craft, Suzanne; Mintz, Akiva
Abstract: We automated radiochemical synthesis of 1-[ 11 C]acetoacetate in a commercially available radiochemistry module, TRASIS AllInOne by [ 11 C]carboxylation of the corresponding enolate anion generated in situ from isopropenylacetate and MeLi, and purified by ion-exchange column resins.1-[ 11 C]acetoacetate was synthesized with high radiochemical purity (95%) and specific activity ( 66.6 GBq/µmol, n = 30) with 35% radiochemical yield, decay corrected to end of synthesis. The total synthesis required 16 min. PET imaging studies were conducted with 1-[ 11 C]acetoacetate in vervet monkeys to validate the radiochemical synthesis. Tissue uptake distribution was similar to that reported in humans. Highlights: Automated and simplified production of 1-[ 11 C]acetoacetate using TRASIS AIO module. 1-[ 11 C]acetoacetate radiochemistry can be directly translated and easily adapted to any automated modules for human injections. 1-[ 11 C]acetoacetate production was validated through monkey PET imaging studies for the first time.